(untitled) (Revista Estudios Psicológicos, 2023)
The present investigation was carried out with the objective of describing the levels of anxiety experienced during the confinement of informal workers located in a municipality in the department of Sucre, Colombia. The research was supported under the quantitative, descriptive, non-experimental methodology. The population consisted of 35 participants assigned to the census previously carried out by a national public institution (municipal mayor’s office). To obtain the necessary information to carry out the study, a Likert scale questionnaire was used. It can be highlighted from the results obtained that the anxiety levels in the study population were not altered by the confinement produced by Covid 19, where 21.8% stated that they had felt irritable at the beginning of the pandemic and of the sample studied. 4 workers showed slight irritability, 2 of them moderately, and the remaining 7 workers became severely irritated due to the confinement caused by the pandemic. It is concluded that the anxiety levels were not directly affected by the confinement by Covid 19, however the stressors are the determinants in the search for tools to reduce its consequences.